2005
DOI: 10.1523/jneurosci.2704-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Functional Specialization in the Human Medial Temporal Lobe

Abstract: Investigations of memory in rats and nonhuman primates have demonstrated functional specialization within the medial temporal lobe (MTL), a set of heavily interconnected structures including the hippocampal formation and underlying entorhinal, perirhinal, and parahippocampal cortices. Most studies in humans, however, especially in patients with brain damage, suggest that the human MTL is a unitary memory system supporting all types of declarative memory, our conscious memory for facts and events. To resolve th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
235
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(266 citation statements)
references
References 41 publications
27
235
4
Order By: Relevance
“…This supports our hypothesis that the perirhinal cortex is involved in object-specific encoding; and the finding corroborates similar results from both the human and non-human primate literature (Aggleton and Brown, 2005;Wan et al, 1999;Bussey et al, 2002Bussey et al, , 2005. Converging evidence from lesion studies of monkeys (Baxter and Murray, 2001), rats (Prusky et al, 2004) and humans (Barense et al, 2005), as well as from neuroimaging studies (Pihlajamäki et al, 2005) have implicated the perirhinal cortex in object processing. Furthermore, studies using immediate early gene imaging in rats indicate that the perirhinal cortex, but not the hippocampus, is involved in processing novel, as opposed to familiar, visual objects.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This supports our hypothesis that the perirhinal cortex is involved in object-specific encoding; and the finding corroborates similar results from both the human and non-human primate literature (Aggleton and Brown, 2005;Wan et al, 1999;Bussey et al, 2002Bussey et al, , 2005. Converging evidence from lesion studies of monkeys (Baxter and Murray, 2001), rats (Prusky et al, 2004) and humans (Barense et al, 2005), as well as from neuroimaging studies (Pihlajamäki et al, 2005) have implicated the perirhinal cortex in object processing. Furthermore, studies using immediate early gene imaging in rats indicate that the perirhinal cortex, but not the hippocampus, is involved in processing novel, as opposed to familiar, visual objects.…”
Section: Discussionsupporting
confidence: 90%
“…It has been suggested that, during encoding, visual object features are processed in the perirhinal and lateral entorhinal cortex, while spatial context is processed in the adjacent medial entorhinal cortex and parahippocampal cortex (Eichenbaum et al, 2007). Indeed, lesions to the perirhinal cortex alone, or together with the entorhinal cortex, have been shown to cause significant deficits in the ability of humans (Barense et al, 2005), monkeys (Baxter and Murray, 2001) and rats (Prusky et al, 2004) to perform visual categorization and memory tasks, deficits not found when lesions are restricted to the hippocampus. It has also been suggested that the memory functions of MTL structures are dissociated according to stimulus content, where the perirhinal cortex contributes more heavily to processing of visual object information (Bussey et al, 2006), while the hippocampus and parahippocampal cortex contribute more in the processing of spatial information (Epstein et al, 1999;Burgess et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the performance of MTL-damaged patients deviated from control performance in two ways: first, they reported seeing the Familiar Configurations as figure somewhat less often than controls, and second, they reported seeing the Part-Rearranged Novel Configurations as figure more often than controls. Taken alone, the first finding is consistent with the theoretical view that the PRC of the MTL contains representations of complex configurations Lee et al, 2005;Barense et al, 2005Barense et al, , 2007Barense et al, , 2010a; Bartko et al, 2007;Lee and Rudebeck, 2010;Burke et al, 2011), and damage to these configural representations removes effects of configuration familiarity on figure assignment. Taken together, however, the two findings suggest that either output from the PRC is privileged over that from lower-level visual regions during figure-ground assignment (a feedforward explanation for the data) or that the intact PRC plays a role in modulating processing in lower-level visual areas (a feedback explanation).…”
Section: Introductionsupporting
confidence: 80%
“…The finding that anterior HPC forms concept-specific representations speaks to the debate on HPC's role in representing complex visual objects (44) and classification learning (4). Although findings from seminal rodent and patient studies suggest perirhinal cortex rather than HPC is critical for processing objects composed of multiple features (45)(46)(47), the current findings are consistent with the account that HPC is important for organizing complex object representations according to changing contexts (39,41,48). Specifically, our results suggest that HPC plays an important role in forming new concepts; these HPC-based concepts may then be consolidated into long-term cortical representations of conceptual Stimulus-specific neural representations from the HPC region in A were used to estimate attention weights to the three feature dimensions.…”
Section: Discussionmentioning
confidence: 99%